1
$\begingroup$

We are given that $C$ is an $n\times n$ complex matrix, and $C$ is Hermitian ($C = C^*$). Now we define $C = A + Bi$ where $A$ and $B$ are real matrices.

Let $M$ be defined by

\begin{bmatrix} A & -B \\ B & A \end{bmatrix}

Given that $\lambda$ is an eigenvalue of $C$ with eigenvector $z = x + iy$, we want to find two independent orthogonal eigenvectors of $M$ with eigenvalue $\lambda$.

I found that

\begin{bmatrix} z \\ -iz \end{bmatrix}

is one eigenvector. How do I find the other one?

$\endgroup$
1
$\begingroup$

Given a Hermitian matrix

$C = C^\dagger \in M_{n \times n}(\Bbb C), \tag 1$

which has an eigenvalue $\lambda$ with associated eigenvector $z$:

$Cz = \lambda z, \tag 2$

it is well-known that

$C^\dagger = C \Longrightarrow \lambda \in \Bbb R; \tag 3$

since the entries of $C$ lie in $\Bbb C$, with real $\lambda$, we will generally have

$z \in \Bbb C^n; \tag 4$

that is,

$z = x + iy, \tag 5$

with

$x, y \in \Bbb R^n; \tag 6$

thus we may write

$C(x + iy) = \lambda(x + iy); \tag 7$

now (1) implies we also have

$C = A + iB, \; A, B \in M_{n \times n}(\Bbb R); \tag 8$

thus (7) becomes

$(A + iB)(x + iy) = \lambda x + i \lambda y, \tag 9$

or

$(Ax - By) + i(Ay + Bx) = \lambda x + i \lambda y; \tag{10}$

equating the real and imaginary parts of either side yields

$Ax - By = \lambda x, \tag{11}$

$Ay + Bx = \lambda y. \tag{12}$

We can now in fact find two real orthogonal eigenvectors for

$M = \begin{bmatrix} A & -B \\ B & A \end{bmatrix}, \tag{13}$

each corresponding to the eigenvalue $\lambda$; set

$w = \begin{pmatrix} x \\ y \end{pmatrix}; \tag{14}$

$Mw = \begin{bmatrix} A & -B \\ B & A \end{bmatrix} \begin{pmatrix} x \\ y \end{pmatrix} = \begin{pmatrix} Ax - By \\ Bx + Ay \end{pmatrix} = \begin{pmatrix} \lambda x \\ \lambda y \end{pmatrix} = \lambda \begin{pmatrix} x \\ y \end{pmatrix} = \lambda w; \tag{15}$

now set

$v = \begin{pmatrix} -y \\ x \end{pmatrix}; \tag{16}$

$Mv = \begin{bmatrix} A & -B \\ B & A \end{bmatrix} \begin{pmatrix} -y \\ x \end{pmatrix} = \begin{pmatrix} -Ay - Bx \\ -By + Ax \end{pmatrix} = \begin{pmatrix} -\lambda y \\ \lambda x \end{pmatrix} = \lambda \begin{pmatrix} -y \\ x \end{pmatrix} = \lambda v; \tag{17}$

furthermore,

$\langle v, w \rangle = \begin{pmatrix} -y \\ x \end{pmatrix}^T \begin{pmatrix} x \\ y \end{pmatrix} = \begin{pmatrix} -y^T & x^T \end{pmatrix} \begin{pmatrix} x \\ y \end{pmatrix} = -y^Tx + x^Ty; \tag{18}$

$y^T x, x^Ty \in \Bbb R \Longrightarrow y^Tx = (y^Tx)^T = x^Ty, \tag{19}$

thus,

$\langle v, w \rangle = 0. \tag{20}$

Note: It may be worth pointing out that the condition on $C$

$C^\dagger = (\bar C)^T = C; \tag{21}$

has implitions for $A$ and $B$ as in (8), for then

$\bar C = A - iB, \tag{22}$

$(\bar C)^T = A^T - iB^T; \tag{23}$

thus,

$A = A^T, \tag {24}$

$B = -B^T; \tag{25}$

we see that $A$, the real part of $C$, must be symmetric, whilst $B$, the imaginary part, must be skew-symmetric. Finally we observe that the matrix $M$ (13) is in fact symmetric as well:

$M^T = \begin{bmatrix} A & -B \\ B & A \end{bmatrix}^T = \begin{bmatrix} A^T & B^T \\ -B^T & A^T \end{bmatrix} = \begin{bmatrix} A & -B \\ B & A \end{bmatrix} = M, \tag{26}$

by virtue of (24)-(25). End of Note.

$\endgroup$
1
$\begingroup$

Try $\ v_1=\begin{bmatrix}x\\y\end{bmatrix}\ $ and $\ v_2=\begin{bmatrix}y\\-x\end{bmatrix}\ $. Your $\ \begin{bmatrix}z\\-iz\end{bmatrix}\ $ is $\ v_1 + iv_2\ $, and $\ v_1-iv_2 =\begin{bmatrix}\overline{z}\\i\overline{z}\end{bmatrix}\ $ is an eigenvector of $\ M\ $ orthogonal to it, and with the same eigenvalue $\ \lambda\ $.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.